2023
DOI: 10.1007/s40279-022-01806-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effects of Static Stretching Exercises on Muscle Strength and Power in Healthy Individuals Across the Lifespan: A Systematic Review with Multi-level Meta-analysis

Abstract: Background The current literature on the chronic effects of static stretching (SS) exercises on muscle strength and power is unclear and controversial. Objective We aimed to examine the chronic effects of SS exercises on muscle strength and power as well as flexibility in healthy individuals across the lifespan. Design Systematic review with meta-analysis of (randomized) controlled trials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 114 publications
1
33
2
Order By: Relevance
“…The study results are in accordance with a growing body of evidence showing high-volume stretch training to sufficiently enhance maximal strength [ 12 , 29 ]. Assuming a dose–response relationship, recent research enhanced the stretching duration up to 2 h per day for 6 weeks [ 30 ], showing highly consistent results in the plantar flexors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study results are in accordance with a growing body of evidence showing high-volume stretch training to sufficiently enhance maximal strength [ 12 , 29 ]. Assuming a dose–response relationship, recent research enhanced the stretching duration up to 2 h per day for 6 weeks [ 30 ], showing highly consistent results in the plantar flexors.…”
Section: Discussionsupporting
confidence: 90%
“…Even though the literature reports alternatives, such as blood flow restriction training [ 9 ] or electromyostimulation [ 10 , 11 ] to induce sufficient stimuli to improve strength, these still require expensive equipment or coaches which might be not available to the broad population. Potentially using stretching as an alternative was suggested by Arntz et al [ 12 ] and Panidi et al [ 13 ] who reported that high-volume and/or high-intensity stretch training could potentially induce improvements in strength capacity. Accordingly, six weeks of one-hour daily self-administered calf muscle stretching induced increases in maximal strength, muscle thickness, and flexibility that were not significantly different from a commonly used resistance training routine (5 × 12 repetitions on 3 days per week for 6 weeks) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increase appeared to be more beneficial for the sedentary than the recreationally active participants. Likewise, chronic static stretching exercises produce marked increases in flexibility with a greater passive effect, compared to active Static Stretching [43].…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of a dispute about the screening of the documents, a third researcher (Third researcher in addition to the authors) discussed the decision of whether to include the documents or not. When the papers had pictures only without raw data and when the data were not obtained after contacting the original authors by email, the raw data were extracted using the chart extraction tool (Arntz et al, 2023; Drevon et al, 2017). Only the most recent publications were included if they belonged to the same study and had the same results (X.…”
Section: Methodsmentioning
confidence: 99%